Genetic Divergence Analysis in Pumpkin: Pumpkin Genetic Divergence - Muhammad Quamruzzaman, Abul Khair; Ahmad, Shahabuddin; Moniruzzaman, Mohammad; Jamil, Mohammad Khalid; Hossain Mollah, Mohammad Amir (Biological Sciences - PJSIR, 2013)